Comparison of Judges' and Clients' Perception of Behavioural and Global Dimensions of Counsellor Relationship - Guttman, M.A. Julius (Canadian Journal of Counselling and Psychotherapy, 1972)
Judges' and clients' ratings of both behavioral and global dimensions of counselor relationship were compared. Results indicated that judges and clients do not perceive the relationship of the counselor similarly. Implications of the findings were discussed.